Effect Of Comfort And Quality Of Service On Consumer Satisfaction At PT. Elephant Mada Indonesia - Daniel; Muhammad Fauzan Azhmy; Saskia (Outline Publisher, 2022)
The purpose of this study was to analyze the effect of comfort and service quality on customer satisfaction at PT. Gajah Mada Indonesia. The data used are primary data and secondary data. Primary data was collected through questionnaires distributed to employees, while secondary data was obtained from documentation studies obtained from various information held by the company and the results of previous research. The data analysis method uses quantitative methods, namely Multiple Linear Regression analysis. The population in this study are consumers or institutions that use the services of PT. Gajah Mada Indonesia (GMI) Medan amounted to 172, the sample of this study used saturated sampling which took the entire population as a sample. The results of the study indicate that Convenience (X1) and Service Quality (X2) together have an effect on Consumer Satisfaction. While the ability of Convenience (X1) and Service Quality (X2) together can explain changes in student Consumer Satisfaction (Y) of 12.5% while the remaining 87.5% is influenced by other factors not discussed in this study.